Peru and the Asia-Pacific Economic Cooperation Forum - Chan Sánchez, Julio (2016)
A brief presentation of the organization, structure and functioning of the Asia-Pacific Economic Cooperation Forum (APEC) is followed by data reaffirming its economic importance. An analysis of trade and investment relations between Peru and APEC is presented as well as of Peru´s progress towards trade and investment liberalization and facilitation (Bogor Goals). Most recent activities related to the Free Trade Area of the Asia-Pacific (FTAAP) are reported, and also Peru´s general theme and priorities, as well as trade priorities for 2016, year in which Peru presides the Forum.